Effect of weed control methods and phosphorus fertilization on growth and yield of clusterbean - Kanwar, Krishna; Yadav, S.S.; Verma, H.P.; Yadav, L.R.; Shivran, A.C. (Annals of Agricultural Research, 2016)
A field experiment entitled "Efficacy of herbicidal weed control in clusterbean at varying levels of phosphorus" was conducted at Agronomy Farm, S.K.N. College of Agriculture, Jobner (Rajasthan) during kharif season of 2013. The results indicated that two HW at 20 and 40 DAS significantly increased plant stand per meter row length, plant height, number of branches per plant, dry matter accumulation per meter row length, number of pods per plant, number of grains per pod, test weight, seed, stover and biological yield and it remained at par with one HW at 20 DAS and application of imazethapyr @ 100 g/ha. Results further indicated that the application of phosphorus @ 60 kg/ha significantly increased plant height, number of branches per plant, dry matter accumulation, number of pods per plant, number of grains per pod, test weight, seed, stover and biological yield and remained at par with the application of phosphorus @ 40 kg/ha. However, plant stand per meter row length remained materially unchanged under different treatments of phosphorus.